Vibration exposure in alpine skiing and consequences for muscle - Federolf, P.; von Tscharner, V.; Haeufle, D.; Nigg, B.; Gimpl, M.; Müller, E. (Science and Skiing IV, 2008)
INTRODUCTION: Strong vibrations are excited at the ski-snow interface (Mester et al., 1999). These equipment vibrations may have an ill effect on motion control (steering quality) and the risk of falls. In this study, time/frequency aspects of equipment vibrations were studied using wavelet analysis. The purpose was to quantify amplitudes and frequencies in short turns, carving turns, and gliding in tuck position at different snow conditions.